Regularly drinking alcohol before sex in the United States: Effects of relationship status and alcohol use disorders() - Thompson, Ronald G. (2014)
BACKGROUND: Drinking alcohol before sex increases the likelihood of engaging in sexual risk behaviors and risk for HIV infection. Relationship status (single versus partnered) and alcohol use disorders (AUD) are associated with each other and sexual risk behaviors, yet have not been examined as predictors of drinking alcohol before sex, using national data. This study examined whether relationship status and AUD increased the likelihood of regularly drinking alcohol before sex in a nationally representative sample. METHODS: The main and additive interaction effects of relationship status and AUD on regularly drinking alcohol before sex were analyzed among sexually active drinkers (N=17,491) from Wave 2 of the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC). Regularly drinking alcohol before sex was defined as drinking alcohol most or all of the time before sex. RESULTS: After adjustment for controls, relationship status (AOR=3.51; CI=2.59–4.75) and AUD (AOR=6.24; CI=5.16–7.53) increased the likelihood of regularly drinking alcohol before sex and interacted to differentially increase this risk, with the effect of being single on the likelihood of regularly drinking alcohol before sex increased among participants with AUD (p<.001). CONCLUSIONS: This study reinforces the importance of relationship status and AUD to the risk for regularly drinking alcohol before sex. Public health efforts should target alcohol and HIV prevention messages to single adults, particularly those with AUD, highlighting their risk for regularly drinking alcohol before sex.